DIGITASI DOKUMEN PENELITIAN ARKEOLOGI - Riyanto, Sugeng (Berkala Arkeologi, 2024)
This paper is prepared with the intention of providing a brief description of the importance of utilizing digital and computer technology in archaeology; about the position and role of digitization in the archaeological research process; and about the digitization process itself, with the hope that it can be "institutionalized", especially at the Balai Arkeologi Yogyakarta.